2021
DOI: 10.1038/s41598-021-95357-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization with mountain hares increases the functional allelic repertoire in brown hares

Abstract: Brown hares (Lepus europaeus Pallas) are able to hybridize with mountain hares (L. timidus Linnaeus) and produce fertile offspring, which results in cross-species gene flow. However, not much is known about the functional significance of this genetic introgression. Using targeted sequencing of candidate loci combined with mtDNA genotyping, we found the ancestral genetic diversity in the Finnish brown hare to be small, likely due to founder effect and range expansion, while gene flow from mountain hares constit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…The evidence for MHC introgression in multiple Triturus hybrid zones provided here adds to a small set of recently published studies indicating that MHC introgression may be a widespread phenomenon. MHC introgression was reported in humans (Abi‐Rached et al, 2011 , MHC‐I), Alpine ibex (Grossen et al, 2014 , MHC‐II), Lacerta lizards (Sagonas et al, 2019 , MHC‐I), Lissotriton newts (Fijarczyk et al, 2018 ; Dudek et al, 2019 , both MHC classes) and hares (Pohjoismäki et al, 2021 , MHC‐II). MHC introgression, with various strengths of supporting evidence, was also suggested for penguins (Hibbets et al, 2020 , MHC‐II), fire‐bellied toads (de Cahsan et al, 2021 , MHC‐II), chickens (Manjula et al, 2021 , MHC region), and trouts (Talarico et al, 2021 , MHC‐II).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for MHC introgression in multiple Triturus hybrid zones provided here adds to a small set of recently published studies indicating that MHC introgression may be a widespread phenomenon. MHC introgression was reported in humans (Abi‐Rached et al, 2011 , MHC‐I), Alpine ibex (Grossen et al, 2014 , MHC‐II), Lacerta lizards (Sagonas et al, 2019 , MHC‐I), Lissotriton newts (Fijarczyk et al, 2018 ; Dudek et al, 2019 , both MHC classes) and hares (Pohjoismäki et al, 2021 , MHC‐II). MHC introgression, with various strengths of supporting evidence, was also suggested for penguins (Hibbets et al, 2020 , MHC‐II), fire‐bellied toads (de Cahsan et al, 2021 , MHC‐II), chickens (Manjula et al, 2021 , MHC region), and trouts (Talarico et al, 2021 , MHC‐II).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that hares represent a widespread radiation of species characterized by striking ecological adaptations and recurrent admixture [ 9 , 46 ]. Based on our preliminary mitochondrial genome data, we speculate the existence of ancient hybridization between L. tanaiticus and L. timidus at the end of the Late Pleistocene; the same as described for L. timidus and L. europaeus [ 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 52%
“…Nowadays, only four hare species inhabit northern Eurasia: brown hare ( L. europaeus ), mountain hare ( L. timidus ), Manchurian hare ( L. mandshuricus ), and Tolai hare ( L. tolai ). Previous studies demonstrated the existence of ancient genomic introgression between Lepus species, particularly between L. timidus and L. europaeus [ 9 , 10 , 11 , 12 ]. Moreover, the hybridization between those species might have an adaptive effect [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introgression may facilitate adaptation of the non-native brown hare to boreal prerequisites (e.g. seasonal shift to white winter pelage 3,7 , cold climate and/or pathogen resistance 9 ). This two-species complex thus offers an excellent model system for exploring how rapid, human-induced ecological change affects species including, their behavioural, demographic and evolutionary interactions over time.…”
Section: Background and Summarymentioning
confidence: 99%